AD, Volume 1, n° 1, 1976 - Full Issue - BUJRA, Abdalla S. (Africa Development, 1976)
Contents A. S. Bujra Editorial ............................... 1 Samir Amin UNCTAD IV and the New International Economic Order ............................ 5 Oscar Braun The New International Economic Order and the Theory of Dependency ...............................12 Cadman Atta-Mills Africa and the New International Economic Order .....................................22 Gabrielle Winai-Strom Socio-Economic Structure and Traditional Authorities in Lesotho ............................28 J. Kombo Moyana The Political Economy of the Migrant Labour System ......................... 34 H. Mapolu & G. Phillipson Agricultural Cooperation and the Development of the Productive Forces: Some Lessons from Tanzania .................... 42 FOCUS ON RESEARCH The Institute for Development Studies .....................59 Institut Fondamental d'Afrique Noire ..................... 61 REVIEWS Janet Bujra Colonial Capitalism and Labour in Kenya 1919-1939 , by R.M.A. Zwanenberg Britain and Kenya 1870-1930: The Economics of Colonialism , by Richard Wolff .............. 67 M. Obeng The Design of Rural Development: Lessons from Africa , by Uma Lele ................... 72 CODESRIA NEWS /CODESRIA ACTIVITIES ............................ 77